PERANCANGAN SISTEM PEREDAM GETARAN PADA MUATAN ROKET RX 320 LAPAN - Djatmiko, Agus Budi (Indonesian Journal of Aerospace, 2010)
Arising vibration of a rocket while flying may cause a damage at electronic equipments, so that the rocket needs to be tested on what extent does the electronic equipment can receive a vibration. Based on the experience during the roll-out of rocket, a GPS (Global of Positioning System) equipment was found out to experience some disturbance as the rocket suffered acceleration , so that it will be difficult to trace the existence of the rocket. To alleviate a vibrating damper systems, we design a GPS for the rocket of RX 320 – LAPAN which is capable to receive the vibration up to 15 g. The result of scheme by comparising two successive amplitudes of X1 / X2 = 1 / 02, spring of stiffness k = 12000 N/m and mass GPS m = 0,3 kg with an acceleration of 15 g, gives the damping coefficient c = 24 N/m/second and resonance amplitude X = 9.2 mm